DETERMINING THE BARRIERS IN ESTABLISHING PROFICIENCY PRESENTATION: ANXIETY AND LANGUAGE INTEGRATION AMONG MANAGEMENT STUDENTS - Vidya Arisandi; Neni Sumarni; Asep Darojatul Romli (Bajang Institute, 2024)
The purpose of this study is to gain insight into the challenges or barriers that a management student encounters when delivering English for Business Management subject matter. The study employed qualitative method. it is reasonable to explicate that the challenge is related to vocabulary mastery, pronunciation, and grammatically correct sentence formation. Nevertheless, his presentation's difficulty is a lack of confidence, as well as missing key critical aspects, such as allowing the audience to ask questions at the end. The use of ordinary English language is deemed more useful than the use of English in business management. This is related to the practice of listening, discovering, learning, and applying it in everyday academic life